Assessment of drinking water quality in hand pump water of Tonk city, Rajasthan, India (International Journal of Scientific Research and Management (IJSRM), 2017)
water is essential for growth and maintenance of life for all living organism at the earth. To study the drinking water pollution in Tonk city of Rajasthan( India), a total of 5 water samples were collected from hand pump of various sites of tonk city. The eleven physical chemical parameters such as pH, Chloride, Total alkalinity, Total dissolved solid(TDS), Total hardness, Iron, Calcium, Sulphate and nitrate and Fluoride were analysed in hand pump water to characterise the ground water quality and suitability for drinking and domestic uses. All the analysed data of hand pump water were compared with Indian standard of drinking water recommended by bureau of Indian standard IS 10500:2012. The physical chemical analysis of hand pump water samples of Tonk city show that pH value ranged from 7.20 to 8.28 and chloride ranged from 86.85mg/l to 960.70 mg/l. The total alkalinity between 396.98 mg/l to 562.80 mg/l. The total dissolved solid ranged from 778mg/l to 3970 mg/l and total hardness from 88.98mg/l to 1156 .76 mg/l. The iron value ranged from 0.0mg/l to 28.79 mg/l, Calcium ranged from 55.55mg/l to 367.81 mg/l and magnesium from 4.09 to 55.74 mg/l . Sulphate ranged from 30.86mg/l to 104.33 mg/l, nitrate from 3.38mg/l to10.13 mg/l and Fluoride varied from 0.1mg/l to 0.3 mg/l. The result of physical chemical analysis of hand pump water samples of Tonk city indicated that hand pump water of sampling site S6 was unsuitable for drinking on the basis of TDS and hand pump water of sampling site S7 was unsuitable for drinking on the basis of TDS, Total hardness and Calcium. Hand pump water of sampling sites S8, S9 and S10 were unsuitable for drinking of the basis of concentration of iron .This study recommended to carry out a strong and continuous water quality program and development of effective practices for utilization of water resources in Tonk city